Plumbagin Induces Reactive Oxygen Species and Endoplasmic Reticulum Stress-related Cell Apoptosis in Human Oral Squamous Cell Carcinoma - CHEN, PO-HAN; LU, HSEIN-KUN; RENN, TING-YI; CHANG, TSUNG-MING; LEE, CHIA-JUNG; TSAO, YA-TING; CHUANG, PO-KAI; LIU, JU-FANG (Anticancer research, 2024)
Oral squamous cell carcinoma (OSCC), a major malignancy in Taiwan, is an invasive epithelial neoplasm resulting in a low survival rate. Current treatments do not prevent OSCC progression, and antitumor therapies should be improved. Plumbagin, a natural compound extracted from Plumbago zeylanica L., appears to have antitumor effects in various tumors. The antitumor mechanism of plumbagin in OSCC is still unclear. This study investigated the molecular mechanism through which plumbagin induces apoptosis. To investigate the antiproliferative and pro-apoptotic effects of Plumbagin on OSCC cells and explore its underlying mechanism, cell counting kit-8, cell cycle analysis, and annexin V/PI assay were conducted. The functions of plumbagin on endoplasmic reticulum (ER) stress, reactive oxygen species (ROS) production, and mitochondrial membrane potential (MMP) deficiency were analyzed using flow cytometric analysis. Plumbagin-induced apoptosis-associated proteins were detected using western blotting. Plumbagin induced apoptosis in OSCC cells by suppressing tumor cell proliferation through ROS production, ER stress, mitochondrial dysfunction, and caspases activation. Plumbagin is a promising antitumor candidate targeting human OSCC.